Rural resources as tourism capital: the case of Setiu Wetlands - Siow, May Ling; Ramachandran, Sridar; Nair, Madhavan Balan; Nair, Vikneswaran; Prabhakaran, Sudesh (2012)
Rural resources are becoming increasingly subjected to pressure from impacts of economic, social, politics and environment. This paper examines the relationship of rural tourism resources and the advantages of adopting sustainable developments policies and strategies based on a case study in Setiu, Terengganu. Few significant steps are taken in deriving these strategies. The first step is identifying the rural capital available in Setiu. The second step is to establish a framework which interact links between rural resources and tourism capital. The third step is to look at the possible investors in rural capital and the final step is to look at the contribution of rural resources towards scaling-up rural tourism. This paper also highlights the profile of rural tourism by re-looking at the rural resource as an ‘asset’ of the rural tourism industry. This case study discusses some of the advantages of re-moulding the rural resource as ‘tourism capital’. An assumption which can be derived is that the rural resource as tourism capital offers a comprehensive and integrated understanding of the rural tourism production system. This will be beneficial if rural communities utilise the potential benefits and effectively handle rural resources. This framework will lead to higher growth utilising tourism capital and thus increasing the standard of living of rural community in Setiu.